The Concept of Equality and Multicultural Justice in Islamic Education - Misalia Sari; Zulkifli; Heny Wulandari; Nilawati Tajudin; Chairul Amriyah (al-Afkar, Journal For Islamic Studies, 2026)
The purpose of this research is to describe and analyze the concept of equality and multicultural justice in Islamic education. This research method uses a qualitative type of literature review research. As for collecting data using books, journal articles, and websites that are relevant to the research title. The results of the study state that the concept of equality is carried out using a formal approach and a substantive approach. In the formal approach this study examines equality based on applicable regulations, both in the form of laws and norms, while the substantive approach examines the concept of equality based on output, as well as the process by which equality occurs. Equality is often associated with gender and social status which characterizes differences and similarities.